Lipid spectrum in liver cells and peripheral blood lymphocytes at children with chronic hepatitis B - V. G. Bulygin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study parameters of lipid composition of liver cells and peripheral blood lymphocytes at children with chronic viral hepatitis B, as well as the relation of these parameters to the stage of disease chronization.Material and methods. Overall 25 children aged 12 to 15 years with chronic hepatitis B were investigated: 14 – had the 2nd stage of hepatitis chronization and 11 – the 3rd stage. Lipid composition parameters were determined by thin-layer chromatography in Silufol with extraction of lipid fractions from cells of liver tissue obtained at guided biopsy, and lymphocytes extracted from venous blood.Results. Metabolic changes in liver tissue of children depend on the stage of chronization of disease, at the 3- rd stage functional lesions of cells are more profound. Metabolism of lymphocytes depends on disease severity as well, thus the 3rd stage is characterized by more severe functional depression of lymphocytes.Conclusions. Intensity of metabolic reactions in liver cells and lymphocytes at 12–15 year old children with chronic hepatitis B depends on the stage of chronization of infectious process and at the 3rd stage more profound changes of investigated parameters were revealed, than at the second. Interrelation pattern of lipid parameters of liver cells and lymphocytes indicate, that the latter mirror specificity and trend of metabolic changes in liver tissue.